2004
DOI: 10.1111/j.1537-2995.2004.03154.x
|View full text |Cite
|
Sign up to set email alerts
|

Sustained suppression of hepatitis C virus by high doses of interferon and ribavirin in adult hemophilic patients

Abstract: High-dose IFN therapy plus ribavirin provided high rates of sustained virologic responses in adult hemophiliacs with chronic HCV, even if side-effects led to dose reduction in half of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
3
13
0
Order By: Relevance
“…Currently, treatment is usually for 6 or 12 months with a combination of pegylated interferon and ribavirin but is toxic and unpleasant; depression and mood changes are often significant. The overall success rate (elimination of the virus) varies with genotype, 70% for genotypes 2 and 3, but is only 29% for the common type 1 (Santagostino et al , 2004). New antiviral agents are under development (Benhamou et al , 2002).…”
Section: Adverse Effects Of Treatmentmentioning
confidence: 99%
“…Currently, treatment is usually for 6 or 12 months with a combination of pegylated interferon and ribavirin but is toxic and unpleasant; depression and mood changes are often significant. The overall success rate (elimination of the virus) varies with genotype, 70% for genotypes 2 and 3, but is only 29% for the common type 1 (Santagostino et al , 2004). New antiviral agents are under development (Benhamou et al , 2002).…”
Section: Adverse Effects Of Treatmentmentioning
confidence: 99%
“…Conversely, combination therapy of IFN 3 MU with 1 g ribavirin for 48 weeks did increase the rates of SVR in adolescents (59%), whereas it had a negligible impact on adult haemophiliacs (15% SVR) [31]. To circumvent IFN resistance, we treated adult haemophilic patients with high doses (5 MU) of IFN and ribavirin, thus achieving higher SVR (41%) [32]. The same treatment schedule was employed to treat patients who previously had not responded to IFN monotherapy, again with satisfactory SVR rates (36%) [33].…”
Section: Interferon Therapymentioning
confidence: 99%
“…Dose reductions were necessary in 26% of the patients due to side effects. The authors concluded that combined therapy overcomes therapeutic failure to monotherapy in one-third of the patients [15,16]. Lower efficacy of monotherapy with interferon in haemophiliacs had already been documented in a previous study [17].…”
Section: Discussionmentioning
confidence: 94%